The Effect of Government Expenditure in the Field of Education, Health and Per Capita Expenditure on the Human Development Index in the Districts/Cities of North Sumatra Province - Faisyal Hartawan Isma; Fitrawaty Fitrawaty; M. Fitri Rahmadana (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine: (1) the effect of government expenditure in the education sector on the Human Development Index (HDI) in the Districts/Cities of North Sumatra Province, (2) the effect of government expenditure in the health sector on the HDI in the Districts/Cities of North Sumatra Province, (3) the effect of per capita expenditure on the HDI in the Districts/Cities of North Sumatra Province, (4) the effect of government expenditure in the education sector, health sector and per capita expenditure on the HDI in the Districts/Cities of North Sumatra Province. This study uses a quantitative approach using secondary data sourced from BPS Indonesia. The data used are panel data of DAK education, DAK health, per capita expenditure and HDI in 33 Districts/Cities of North Sumatra Province from 2018-2024 or as many as 231 observations. The data analysis technique in this study uses panel data regression with the Eviews 10 program application with the best selected estimation model, namely the fixed effect model (FEM). The results of this study indicate that: (1) government expenditure in the field of education has a positive and significant effect on the HDI in the Regency/City of North Sumatra Province, (2) government expenditure in the field of health has a positive and significant effect on the HDI in the Regency/City of North Sumatra Province, (3) per capita expenditure has a positive and significant effect on the HDI in the Regency/City of North Sumatra Province, (4) government expenditure in the field of education, health and per capita expenditure simultaneously have a significant effect on the HDI in the Regency/City of North Sumatra Province. Furthermore, the area with the best HDI model is in Padang Sidempuan Regency, while the area with the lowest HDI model is in Serdang Berdagai Regency.